Contemporary Drug-Eluting Stents and Functional Recovery After Percutaneous Coronary Intervention: Implications for Exercise Capacity and Cardiac Rehabilitation - Czechowicz, Justyna; Czechowicz, Paweł; Antkiewicz, Mikołaj; Arczyńska-Antkiewicz, Aleksandra; Drozd, Maria; Kruczek, Zuzanna; Kociuba, Julia; Kołkowicz, Dorota; Pawełczak, Natalia; Krawczyk, Agata; et al. (Quality in Sport, 2026)
Background. Technological advances in contemporary drug-eluting stents (DES) have significantly improved the safety and effectiveness of percutaneous coronary intervention (PCI). However, most studies focus on traditional clinical endpoints, while the impact of modern PCI technologies on functional recovery and return to physical activity remains less well defined. Aim. This review aimed to examine the relationship between contemporary PCI, vascular healing, and restoration of exercise capacity, with particular emphasis on cardiac rehabilitation. Material and methods. A narrative review of current literature was performed, focusing on vascular healing after PCI, endothelial recovery with newer-generation DES, thrombotic and bleeding risks during exercise, and the role of exercise-based cardiac rehabilitation. Results. Modern DES characterized by thinner struts and improved biocompatibility are associated with enhanced vascular healing and lower rates of late stent thrombosis. These features may support safer return to physical activity. However, exercise capacity depends not only on coronary patency but also on microvascular function, peripheral conditioning, and participation in rehabilitation programs. Cardiac rehabilitation plays a key role in improving fitness, quality of life, and long-term physical activity. Conclusions. Contemporary PCI provides a stable basis for safe rehabilitation and physical activity. Optimal recovery requires integration of interventional treatment with structured exercise programs and individualized management. Future studies should include standardized functional outcomes.